Sub‐microsecond‐resolved multi‐speckle X‐ray photon correlation spectroscopy with a pixel array detector. (2nd August 2018) - Zhang, Qingteng; Dufresne, Eric M.; Narayanan, Suresh; Maj, Piotr; Koziol, Anna; Szczygiel, Robert; Grybos, Pawel; Sutton, Mark; Sandy, Alec R.
Abstract : Sub‐microsecond‐resolved multispeckle XPCS spanning nearly eight orders of magnitude in delay times is demonstrated using the UFXC32k area detector in a combination of burst and continuous data acquisition modes. Abstract : Small‐angle X‐ray photon correlation spectroscopy (XPCS) measurements spanning delay times from 826 ns to 52.8 s were performed using a photon‐counting pixel array detector with a dynamic range of 0–3 (2 bits). Fine resolution and a wide dynamic range of time scales was achieved by combining two modes of operation of the detector: (i) continuous mode, where data acquisition and data readout are performed in parallel with a frame acquisition time of 19.36 µs, and (ii) burst mode, where 12 frames are acquired with frame integration times of either 2.56 µs frame −1 or 826 ns frame −1 followed by 3.49 ms or 1.16 ms, respectively, for readout. The applicability of the detector for performing multi‐speckle XPCS was demonstrated by measuring the Brownian dynamics of 10 nm‐radius gold and 57 nm‐radius silica colloids in water at room temperature. In addition, the capability of the detector to faithfully record one‐ and two‐photon counts was examined by comparing the statistical distribution of photon counts with expected probabilities from the negative binomial distribution. It was found that in burst mode the ratio of 2 s to 1 s is markedly smaller than predicted and that this is attributable to pixel‐response dead‐time.